2020
DOI: 10.1097/md.0000000000019718
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for erectile dysfunction in post-stroke patients

Abstract: Introduction: Erectile dysfunction refers to the continued inability of the penis to reach and maintain sufficient erections to achieve a satisfactory sex life and last at least 6 months. As part of traditional Chinese medicine, acupuncture has been widely used in clinical practice. In order to evaluate, the exact effect of acupuncture on the clinical efficacy of patients with Post-stroke Erectile dysfunction (PSED), this experiment uses randomized controlled experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In other studies, Tibaek et al ( 60 ) showed that pelvic floor muscle training might be beneficial to stroke men with ED. A randomized controlled trial developed by Li et al ( 61 ) showed that acupuncture was a safe and effective treatment for post-stroke ED.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, Tibaek et al ( 60 ) showed that pelvic floor muscle training might be beneficial to stroke men with ED. A randomized controlled trial developed by Li et al ( 61 ) showed that acupuncture was a safe and effective treatment for post-stroke ED.…”
Section: Discussionmentioning
confidence: 99%